극한 환경하의 부표 운동성능 모형시험기법 개발 - 홍기용(KEYYONG HONG); 양찬규(CHAN-KYU YANG); 최학선(HARK SUN CHOI) (Han-guk haeyang gonghak hoeji (Online), 2001)
An experimental method to investigate the dynamic characteristics of buoys in extreme environmental condition is established. Because the buoy model requires a resonable size for accurate experiment, the test condition in model basin that satisfies the similarity law is hardly compatible with capability of test facilities. It is suggested that the linear wave component that is unable to satisfy similarity is separated with others. The model experiment is carried out with mitigated condition for the linear wave components while others including wave drift, current and wind are keeping the similarities. Then, the result can be extrapolated to give the dynamic behavior of buoys n extreme condition because linear wave component is solely responsibly to oscillatory buoy motion and other environmental components are applied as a initial tension. The similarity for current and wind conditions is viewed as equivalence of restoring forces. The validity of proposed method is examined with different types of standard ocean buoys and it indicates that the linearity of measured characteristics is assured with a limitation of resonable distance between test and estimated wave conditions.